2013
DOI: 10.1002/pro.2254
|View full text |Cite
|
Sign up to set email alerts
|

A multipurpose fusion tag derived from an unstructured and hyperacidic region of the amyloid precursor protein

Abstract: Expression and purification of aggregation-prone and disulfide-containing proteins in Escherichia coli remains as a major hurdle for structural and functional analyses of high-value target proteins. Here, we present a novel gene-fusion strategy that greatly simplifies purification and refolding procedure at very low cost using a unique hyperacidic module derived from the human amyloid precursor protein. Fusion with this polypeptide (dubbed FATT for Flag-Acidic-Target Tag) results in near-complete soluble expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…We have so far tested >20 different antibody clones from various species and subclasses (Table 2 and data not shown) for the conversion into Fv-clasp format, and all were successfully refolded from the denatured inclusion bodies using the universal protocol shown in Figure S1. Of particular note, the list includes antibodies that cannot be efficiently refolded into scFv, namely SG/19, 12CA5, and 9E10 (Fujiwara et al, 2002;Sangawa et al, 2013). This strongly suggests that holding the bottom of the Fv by the SARAH domain coiled coil greatly facilitates the overall (re) folding, probably by increasing the chance of the optimum encounter between V H and V L , which may otherwise be relatively inefficient.…”
Section: Discussionmentioning
confidence: 99%
“…We have so far tested >20 different antibody clones from various species and subclasses (Table 2 and data not shown) for the conversion into Fv-clasp format, and all were successfully refolded from the denatured inclusion bodies using the universal protocol shown in Figure S1. Of particular note, the list includes antibodies that cannot be efficiently refolded into scFv, namely SG/19, 12CA5, and 9E10 (Fujiwara et al, 2002;Sangawa et al, 2013). This strongly suggests that holding the bottom of the Fv by the SARAH domain coiled coil greatly facilitates the overall (re) folding, probably by increasing the chance of the optimum encounter between V H and V L , which may otherwise be relatively inefficient.…”
Section: Discussionmentioning
confidence: 99%
“…Sangawa et al (24) described a fusion tag that enhanced solubility of a wide range of proteins. Their FATT tag is a ϳ130-amino acid peptide that is intrinsically disordered and highly acidic.…”
Section: Expression Of Soluble Gsftsz Using the Fatt Tag Vector-mentioning
confidence: 99%
“…We have confirmed that chloroplast FtsZ from several species were insoluble when expressed in E. coli. We therefore adapted a recently described fusion system, termed the "FATT tag" (24), and this has given expression of several chloroplast FtsZs as soluble proteins.…”
mentioning
confidence: 99%
“…and M.S., unpublished results). To promote efficient solubilization of the Zip3 protein, we used the extremely acidic FATT(-Myc) epitope tag (Sangawa et al, 2013) and found that the FATT-tagged Zip3 protein was soluble in E. coli lysates. The FATT-Zip3 was bound to magnetic beads coated with anti-Myc antibodies and incubated with extracts of yeast meiotic cells expressing RAD17-HA DDC1-Flag.…”
Section: Interaction Of Zip3 With the Checkpoint Clamp In Vitromentioning
confidence: 99%
“…A ZIP open reading frame was placed under the control of the T7 promoter of an expression vector, pFATT3 (Sangawa et al, 2013) by the SLIC method (Li and Elledge, 2007). FATT-Zip3-expressing E. coli cells were disrupted by sonication in lysis buffer (50 mM Hepes-KOH pH 7.5, 300 mM KCl, 20% v/v glycerol, 1 mM NaVO 3 , 60 mM bglycerophosphate and 0.1% v/v NP-40) and cell lysates were applied to magnetic beads (GE Healthcare) coated with anti-c-Myc antibodies.…”
Section: Zip3 Pulldown Assaymentioning
confidence: 99%